An Extended Kalman Filter for Nonsmooth Attitude Control Design of Quadrotors using Quaternion Representation - Adha Cahyadi; Andreas P. Sandiwan; Samiadji Herdjunanto (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2022)
This paper proposed Extended Kalman Filter specifically designed for nonlinear and nonsmooth control system applied in Autonomous Quadrotor Control such as sliding mode control. Many controllers focused on global stability usually consider exact parameters through measurements. Such assumptions are not always possible due to the unavailability of sensors or unmeasurable state in real-life condition. In this paper, we consider only the angular velocity is possible for measurement, i.e., only gyroscope measurement is available. This condition is known as omega-state-measurement (OSM). Without loss of generality, for theoretical simplification beside gyroscope measurement, we assume the orientation measurement represented in quaternion is also available. Additive random gaussian noise is included to the measurement model to be used in Kalman Filter. Finally the proposed Extended Kalman Filter implemented in a PD Sliding Mode controller is simulated using many scenarios to verify its effectiveness. The Kalman Filter works well in spite of model error and disturbance.